Image Encryption Technique Based on Pixel Exchange and XOR Operation - Kiswara A. Santoso; Fatmawati Fatmawati; Herry Suprajitno (UPT Penerbitan Universitas Jember, 2016)
Recently the information system develops quickly, especially information system via internet. It’s happened because the Internet can be used by anyone, anywhere and anytime. The information on the Internet has various types of data such as text, video, audio, and image/photo. Although we can access the Internet easily, but the data which transfered through internet isn’t safe. It caused by hacker, someone who manipulate information so that data become diﬀerent with the original. Many eﬀorts have been done to make the data that transmitted over the Internet to be secure, for example make the coding, disguise or hide data into other media. In this paper we intend to present the results of research about image encryption techniques to increase the security of data (image) so that safe if the data is transfered via the internet. This encryption using symmetric-key. The key is 4 BIT or a real number between 0 15. This key will be processed by each pixel in the image using XOR operation. The next step the BIT of pixels are devided into two part, LSB (least signiﬁcant bit) and MSB (Most signiﬁcant bit). Both will be exchanged if the conditions have completed. We do that to get better results, that is ﬁle size of the image encryption is smaller than the original image. The results of this research are image encryption have signiﬁcant diﬀerences with the original image, it can be proved by correlation between both images. Another advantage of this coding technique is the image encryption ﬁle size smaller than the original image ﬁle size so it can speed up of image transfer. Decode result of this coding technique is good enough, it can be seen from the mean square error (MSE) between the image encryption that has been restored to its original form and the original image. All the manufacturing process of encoding techniques have been simulated and analyzed using software MATLAB 2012a.